The Studi Komparasi Penggunaan E-Booklet Dan Buku Saku Terhadap Pengetahuan Ibu Hamil Tentang Pencegahan Anemia Di Wilayah Kerja Puskesmas Martapura 2 Tahun 2024 - Azzahra, Refina; Suhrawardi, Suhrawardi; Hipni, Rubiati; Kirana, Rita (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2024)
Anemia among pregnant women in Indonesia is still high, reaching 48.9%, which can cause serious pregnancy complications. To analyze the difference in effectiveness between the use of e-booklets and pocketbooks in improving pregnant women's knowledge about anemia prevention in the working area of Puskesmas Martapura 2.This study used a quantitative method with a quasy-experiment design, involving two experimental groups: the e-booklet group and the pocket book group. The study population was pregnant women in the working area of Puskesmas Martapura 2, with purposive sampling technique. Data were collected through questionnaires distributed using Google Form to assess pregnant women's knowledge about anemia prevention before and after the intervention. Data were analyzed using the Mann-Whitney test to compare the effectiveness of the two educational media. The results showed that both methods were considered equally effective in increasing pregnant women's knowledge about anemia prevention (E-Booklet p=0.097 and Pocket Book p=0.155). There was no difference between the use of e-booklets and pocketbooks. Both methods are equally effective in improving pregnant women's knowledge about anemia prevention. Keywords: Anemia, pregnant women, e-booklet, pocket book, knowledge